Aerodynamics of cycling - Martin, J.
The cycling power required for any velocity can be predicted based on a mathematical equation, and you can get a rough estimate of your cycling power based on your 10k run time. In general, the slower the rider, the more improvement he/she can expect from improved aerodynamics. The biggest changes in aerodynamic drag and in cycling performance come from changes in body position, which can improve 40k time by over 6 minutes. An excellent position on a regular bike with regular wheels will allow you to out perform a rider with a typical position on an aero bike with aero wheels by 3 to 4 minutes. Aero wheels can reduce drag by about 0.4 lb. and will reduce your 40k time by about 1 to 2 minutes. An aero frame can reduce drag an additional 0.3 lb. and save you about an additional minute. The effects of bicycle weight, even on a tough climbing course are minimal compared with the effects of aerodynamics. Windy conditions slow you down because you spend more time in the headwind than you do in the tailwind, so it doesn't 'average out'. Finally, the time saved by changes in position and equipment is similar for larger and smaller riders.